PETA JALAN SMART BUMDes: TATA KELOLA MANAJEMEN DAN KEUANGAN GO DIGITAL - Afrah Junita; Tuti Meutia; Riny Chandra (LPPM dan PM Universitas Samudra, 2021)
-Village-Owned Enterprise (BUMdes) “Mitra Usaha Mandiri” Gampong Meurandeh Dayah Langsa Lama District is an organization that was only established in 2015. The formation of BUMdes Mitra Usaha Mandiri is a form of village government efforts to increase the village's original opinion and improve the livelihood of Meurandeh Dayah villagers. However, without good management and support from the government and the community, the hope of making this BUMdes a SMART BUMDes and locomotype of the village economy cannot be realized. On the other hand, the sustainability of BUMDes will be very much determined by how BUMDes administrators can carry out management and financial management, so that the BUMDes road map to SMART BUMDes can be realized. This Community Service aims to assist BUMDes administrators in carrying out management and financial management by using the mentoring method for the results of the training that BUMDes administrators will undertake. This service program is expected to foster a good understanding of good digital-based management and financial governance.